El Liderazgo en la Gestión Administrativa del Centro de Educación General Básica Intercultural Bilingüe “Humberto Vacas Gómez” de la comuna Cuturiví Chico del cantón Pujilí, provincia de Cotopaxi en el año 2016. Propuesta: Estrategias de Liderazgo. - Tutín Rea, María Hortencia (2017)
This research aims to analyze the problem of how the Leadership in Administrative Management at “Humberto Vacas Gómez" intercultural bilingual basically education is affected, for which it has been proposed as a general objective to fortify the Administrative Management through the application of leadership strategies that allow to achieve the improvement of the educational quality. The hypothesis that seeks to clear, is to verify if the leadership affects the administrative management in the Center. The methodology used is based on a qualitative-quantitative approach using the questionnaire as the main instrument. As a conclusion, it has been possible to determine that the educational actors are dissatisfied with the leadership that is setting up in the educational institution because they consider authoritarian, not inclusive, unconscious and undemocratic, which has greatly impaired interpersonal relations and therefore the quality of the administrative management is deficient. Leadership is a set of skills and strategies that can be innate in nature, that is to say that is born with the human being and others acquired through the experience, social and human coexistence that makes a person with special characteristics. The deductive method should be considered as the most capable to develop leadership actions, since the leader plans, motivates and executes activities, actions in which their leaders must discern, analyze and reflect deeply to decide the best administrative option. It is essential to point out that there is an important predisposition of the educational actors for participation in the generation of a proposed solution to the problem raised.